2018
DOI: 10.1021/acs.jafc.8b00152
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Innate Immune Function by Panax ginseng after Heat Processing

Abstract: Panax ginseng Meyer has been used for the treatment of immune diseases and for strengthening the immune function. In this study, we evaluated the innate immune-stimulating functions and action mechanisms of white ginseng (WG) and heat-processed ginseng (HPG) in RAW264.7 cells. According to LC-MS analysis results, WG contained typical ginsenosides, such as Rb1, Rc, Rb2, Rd, and Rg1, whereas HPG contained Rg3, Rk1, and Rg5 as well as typical ginsenosides. HPG, not WG, enhanced NF-κB transcriptional activity, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…However, the pharmacological activities of red ginseng have not been attributed to ginsenosides. Recently, several studies reported that Korea red ginseng-derived polysaccharides showed immune-enhancing activities such as macrophage activation, cytokine production mediated by Peyer’s patches, and splenic lymphocyte proliferation in vitro and in vivo [ 19 , 20 , 21 , 22 , 23 ]. Nonetheless, there are few studies on the effects of polysaccharides from Korea red ginseng (KRG) on IgA production via Peyer’s patch activation and α-defensin expression for maintaining intestinal homeostasis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pharmacological activities of red ginseng have not been attributed to ginsenosides. Recently, several studies reported that Korea red ginseng-derived polysaccharides showed immune-enhancing activities such as macrophage activation, cytokine production mediated by Peyer’s patches, and splenic lymphocyte proliferation in vitro and in vivo [ 19 , 20 , 21 , 22 , 23 ]. Nonetheless, there are few studies on the effects of polysaccharides from Korea red ginseng (KRG) on IgA production via Peyer’s patch activation and α-defensin expression for maintaining intestinal homeostasis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The various health-promoting effects of RG have been reported to include alleviation of fatigue, protection from muscle damage after strenuous exercise, and improvements in energy metabolism [21][22][23][24]. Red ginseng has been reported to show an increase in multiple types of ginsenosides compared to white ginseng, including Rg3, Rk1, Rf, and Rg5 [25,26]. Rg3 was previously reported to display anti-fatigue effects [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the contents of malonylginsenoside-Rb1, -Rc, -Rb3, -Rd, -Rb2, -Rg1, and -Re, and ginsenoside-Re5 in all the WG samples were significantly higher.. This was illustrated in the heating trial, in which the concentration of ginsenosides was affected by the thermal processing condition and the degree of conversion between malonyl and neutral ginsenosides [ 37 , 42 , 43 ]. The results suggested that malonyl-ginsenoside was thermally unstable and especially susceptible to hydrolysis by extruding treatment.…”
Section: Resultsmentioning
confidence: 99%